(untitled) (CIPEEX, 2026)
This paper aims to analyze the relevance of therapist feelings in contextual behavioral therapies, such as Functional Analytic Psychotherapy (FAP), Acceptance and Commitment Therapy (ACT), Dialectical Behavior Therapy (DBT), and Integrative Behavioral Couple Therapy (IBCT). In these approaches, the therapist’s feelings are not merely private events, but rather instruments that guide clinical choices, strengthen the therapeutic relationship, and serve as intervention resources. The objective of this study is to understand how therapist feelings are perceived and used within the therapeutic process, based on Grounded Theory. The research explores the benefits of self-disclosure, emotional sensitivity, and clinical awareness as elements that enhance the effectiveness of the therapeutic relationship. By recognizing feelings as an integral part of the therapist-client interaction, this investigation seeks to highlight that clinical practice can be enriched by the professional’s openness and careful management of their emotions.